P320 Confocal Laser Endomicroscopy to predict the efficacy of vedolizumab as first-line biotherapy in ulcerative colitis. (30th January 2023) - Quénéhervé, L; Trang-Poisson, C; Fantou, A; Flamant, M; Durand, T; Bouguen, G; Bregeon, J; Oullier, T; Amil, M; Dewitte, M; Bardot, S; Braudeau, C; et al.
Abstract: Background: There is no biomarker to guide first-line of biotherapy in ulcerative colitis (UC). The main objective of this multicenter pilot study was to demonstrate the feasibility of identifying a4b7 and/or TNF-a expressing cells by dual-band confocal endomicroscopy (CLE) into the mucosa to predict the response to vedolizumab as first-line biotherapy. NCT02878083. Methods: Patients with moderate to severe UC, naïve of biotherapy were prospectively included and received vedolizumab. Patients were evaluated clinically, biologically, endoscopically and histologically at week 22. Nonresponding patients were subsequently treated by adalimumab and were evaluated at week 30. Prior to the initiation of vedolizumab, during endoscopy, 8 biopsies were taken for extemporaneous and ex vivo analysis by CLE, histology and confocal microscopy. Fresh biopsies were treated with vedolizumab coupled with FITC and adalimumab coupled with Alexa-Fluor to analyze their respective fluorescence (figure) in one step with the Dual-band CLE system (Mauna Kea Technologies, France). The number and the surface of positive stained areas visualized by CLE were counted and compared between responders and non-responders. Blood samples were collected before each infusion and were used to analyze the immune cells (LT, LB, NK, monocytes) by FACS and vedolizumab trough levels. Frozen biopsies were analyzed by confocal microscopy (Opal Akoya multiplexing; Tyramide signal amplification) after labeling by an anti-a4b7 antibody. Results: 19 patients out of the 20 initially planned were included. Clinical remission, endoscopic improvement (Mayo ≤ 1), endoscopic remission (Mayo 0) at W22 were respectively 58%, 58% and 45%. 18 out of 19 patients (95%) could be analyzed by CLE. The number and surface of vedolizumab-FITC stained areas were numerically superior in responder patients at week22; by contrast, no difference was found for the areas marked by adalimumab-Alexa-fluor. A threshold value of 6 areas marked in CLE by the vedolizumab-FITC at week 0 discriminated responders and non-responders at week 22 with a Se of 78% and a Sp of 85%. No difference of circulating cell population has been identified between responders and non-responders and the vedolizumab trough levels were not predictive of the response. In confocal microscopy, 15 patients have been analyzed; the percentage of a4b7-binding cells was not different between responders (n=9) and non-responders (n=6) Conclusion: This study confirms the feasibility of extemporaneous identification by dual-band CLE of the mucosal cells expressing a4b7 and/or TNF-a. Results suggest that only the proportion of cells binding vedolizumab-FITC in the mucosa was indicative of the response to vedolizumab